Deep learning infused SIRVD model for COVID-19 prediction: XGBoost-SIRVD-LSTM approach - Alkhalefah, Hisham; Preethi, D.; Khare, Neelu; Abidi, Mustufa Haider; Umer, Usama (Frontiers in Medicine, 2024)
The global impact of the ongoing COVID-19 pandemic, while somewhat contained, remains a critical challenge that has tested the resilience of humanity. Accurate and timely prediction of COVID-19 transmission dynamics and future trends is essential for informed decision-making in public health. Deep learning and mathematical models have emerged as promising tools, yet concerns regarding accuracy persist. This research suggests a novel model for forecasting the COVID-19's future trajectory. The model combines the benefits of machine learning models and mathematical models. The SIRVD model, a mathematical based model that depicts the reach of the infection via population, serves as basis for the proposed model. A deep prediction model for COVID-19 using XGBoost-SIRVD-LSTM is presented. The suggested approach combines SIRVD (Susceptible-Infected-Recovered-Vaccinated-Deceased), and a deep learning model, which includes LSTM (Long Short-Term Memory) and other prediction models, including feature selection using XGBoost method. The model keeps track of changes in each group's membership over time. To increase the SIRVD model's accuracy, machine learning is applied. The key properties for forecasting the spread of the infection are found using a method called feature selection. Then, in order to learn from these features and create predictions, a model involving deep learning is applied. The performance of the model proposed was assessed with prediction metrics such as R 2 , RMSE (root mean square error), MAPE (mean absolute percentage error), and NRMSE (normalized root mean square error). The results are also validated to those of other prediction models. The empirical results show that the suggested model outperforms similar models. Findings suggest its potential as a valuable tool for pandemic management and public health decision-making.